Inflammatory and nutritional markers predict the risk of post-operative delirium in elderly patients following total hip arthroplasty - Hu, Wenhao; Song, Ziyi; Shang, Houlai; Wang, Jingcheng; Hao, Yuedong (Frontiers in Nutrition, 2023)
Objectives: This study intended to explore whether albumin-associated nutritional markers could predict postoperative delirium (POD) in older patients after total hip arthroplasty (THA). In addition, we established a nomogram model for POD prediction.: Totally, 254 elderly cases who received THA were included. Clinical and laboratory data of these patients were retrospectively collected. Albumin-associated nutritional markers included neutrophil-to-albumin ratio (NAR), CRP-to-albumin ratio (CAR), prognostic nutritional index (PNI), and systemic inflammation score (SIS). The LASSO, univariate and multivariate logistic regression analyses were utilized to screen risk factors. A nomogram model was developed according to the results of multivariate regression analyses. Results: Among 254 patients, 49 cases had POD with an incidence of 19.3%. LASSO regression and multivariate logistic analyses suggested that preoperative NAR, preoperative PNI, preoperative SIS, and age > 75 years were risk factors for POD. A nomogram model was developed according to the results of multivariate logistic analyses. The calibration curve suggested that the predicted probability of this nomogram model was in good line with the actual probability. The DCA showed that this nomogram model had net benefits for the prediction of POD for elderly patients following THA. Conclusions: Albumin-associated nutritional markers including NAR, PNI, and SIS could predict POD in elderly patients following THA.